2020
DOI: 10.7759/cureus.8002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dual-Energy Computed Tomography in Characterization of Ureteric Calculi and Urinary Obstruction

Abstract: The present study was carried out to assess the accuracy of dual-energy computed tomography (DECT) in the morphological and chemical characterization of ureteric calculi along with the prediction of the grade of urinary obstruction. Methods This was a prospective observational study that included 100 cases with ultrasonography (USG)-diagnosed ureteric calculi that underwent surgery or had spontaneous expulsion of ureteric calculi. At enrolment, DECT was performed for an in vivo evaluation of volume, chemical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…For stones which are a mixture of several stone types, the results of DECT were completely inaccurate. Overall, the present results are consistent with the findings of previous research (13)(14)(15). In conclusion, based on the results of this brief research, for an accurate detection of all pure and mixed renal stones, further analytical methods are needed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For stones which are a mixture of several stone types, the results of DECT were completely inaccurate. Overall, the present results are consistent with the findings of previous research (13)(14)(15). In conclusion, based on the results of this brief research, for an accurate detection of all pure and mixed renal stones, further analytical methods are needed.…”
Section: Discussionsupporting
confidence: 92%
“…Dual-energy CT (DECT) scanning, which is known as one of the most promising developments in radiology, is used for determining the components of different materials or material identification (9). Several studies have reported the clinical benefits of DECT in the identification of renal stone types (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the detection sensitivity of urinary calculi with lengths <three mm was high ( Spek et al, 2016 ). A previous study found that most ureteral stones with lengths of less than three mm can be excreted by themselves, although even if the length of the stone is less than three mm, it can cause pain and microscopic hematuria ( Singh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of DECT to differentiate various materials has been applied in the components analysis of urinary stones in the field of urology, with a reported diagnostic accuracy of over 80% [9]. We anticipate that DECT will become widely applicable in various cases in the future.…”
Section: Discussionmentioning
confidence: 99%